Barriers Remain: Perceptions and Uses of Comics by Mental Health and Social Care Library Users. Issue 2 (17th July 2020) - Farthing, Anthony; Priego, Ernesto
This article is part of a larger study investigating the perceived value of using comics as an information resource in the teaching and training of mental health and social care professionals in a higher education setting. We surveyed 108 library users at the Tavistock and Portman NHS Foundation Trust, which specialises in mental health and social care and is a centre for both treatment and training. The study showed that most participants believed that comics have a potential role to play in mental health care training, and that challenges remain in getting comics perceived in ways that are not limited by existing prejudices or socio-cultural assumptions. Amongst other findings, the study found no significant association between the age or gender of participants and their attitudes to comics in an academic context. Participants considered that the most useful application of comics within the mental health and social care domain was their potential use in medical or therapeutic settings with young people. Even when our sample was not dominated by participants who reported reading comics regularly, the study showed that recent experience of reading comics seems to positively influence how comfortable participants feel about using comics for teaching or learning.